Thermo-hydraulic rating of a shell and tube heat exchanger for methanol condensation (Nexo Revista Científica, 2022)
Shell and tube heat exchangers are the most common type of heat exchangers, and are applicable for a wide range of operating temperatures and pressures. In the present work the thermo-hydraulic rating of a shell and tube heat exchanger was carried out, in order to perform the condensation of a methanol stream using water as coolant. The overall heat transfer coefficient for both the sensible-heat and latent-heat zone had values of 166.41 W/m2.K and 1,198.39 W/m2.K, respectively; while the required total heat transfer area and percent excess area had values of 38.08 m2 and 3.05 %, respectively. The pressure drops of methanol and water streams reached the values of 51,490.84 Pa and 2,890.50 Pa, respectively. The proposed shell and tube heat exchanger can be employed satisfactorily for the demanded heat transfer service, since the calculated percent excess area does not exceed 25%, and the pressure drop of the water stream does not exceed the value of 80,000 Pa.